2006
DOI: 10.1111/j.1574-6968.2006.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of enteropathogenic and enterohaemorrhagicEscherichia colipathogenesis

Abstract: This review covers enteropathogenic Escherichia coli (EPEC) and enterohaemorrhagic E. coli (EHEC) infections, focusing on differences in their virulence factors and regulation. While Shiga-toxin expression from integrated bacteriophages sets EHEC apart from EPEC, EHEC infections often originate from asymptomatic carriage in ruminants whereas human EPEC are considered to be overt pathogens and more host-restricted. In part, these differences reflect variation in adhesin repertoire, type III-secreted effectors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
105
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 115 publications
(196 reference statements)
0
105
0
4
Order By: Relevance
“…Only the magnitude of the change varied when strains were examined without epithelial cell exposure. Regulation of the LEE is complex and is influenced by multiple environmental factors that act on several chromosomal genes, which in turn fine-tune LEE expression through LEE-encoded regulators, Ler, GrlA and GrlR (Deng et al, 2004;Spears et al, 2006). Once activated, Ler leads to induction of operons LEE2, LEE3, LEE5 and LEE4 (Barba et al, 2005;Haack et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only the magnitude of the change varied when strains were examined without epithelial cell exposure. Regulation of the LEE is complex and is influenced by multiple environmental factors that act on several chromosomal genes, which in turn fine-tune LEE expression through LEE-encoded regulators, Ler, GrlA and GrlR (Deng et al, 2004;Spears et al, 2006). Once activated, Ler leads to induction of operons LEE2, LEE3, LEE5 and LEE4 (Barba et al, 2005;Haack et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed differential expression of Shiga toxins (Stx1, 2 and variants), which are critical for HUS pathogenesis (Kaper et al, 2004), among strains from distinct O157 : H7 subpopulations (de Sablet et al, 2008;Dowd & Williams, 2008). In addition, expression of the locus of enterocyte effacement (LEE) genes, which encode a type III secretion system (TTSS) that mediates intimate attachment and yields attaching/effacing (A/E) lesions (McDaniel et al, 1995), is influenced by distal regulators, chromosomal and plasmid borne (Kaper et al, 2004;Spears et al, 2006). Distinct differences in LEE regulation have been observed between closely related intestinal E. coli pathogens (Spears et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more severe disease outcomes are caused by a subset of STEC termed enterohaemorrhagic E. coli (EHEC), which includes the O157 : H7 serogroup Riley et al, 1983). EHEC possess an array of virulence factors that enhance survival and invasion in the gut, but the principal factor associated with the most severe sequelae, haemolytic uraemic syndrome (HUS) and thrombotic thrombocytopenic purpura (TTP), is the production of Shiga toxin (Stx) (Kaper et al, 2004;Spears et al, 2006). It has recently been proposed that Stx overexpression in E. coli O157 : H7 strains is associated with severe human disease (Neupane et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, EPEC is a significant cause of infantile diarrhea, which is associated with a high rate of mortality (10-40%). 2 In the last decade, identification and characterization of several EPEC virulence factors have significantly contributed to our understanding of EPEC pathogenesis, especially with regard to their effects on basic intestinal epithelial functions. Nevertheless, the complete mechanism underlying EPEC-induced diarrheal illness remains elusive.…”
mentioning
confidence: 99%